1. выражение: а) (х-3)(х+3) + (х+3)^2 б) (у-4)^2 - (4-у)(4+у) 2. решите уравнение: а) (2х + 3)^2 - 7x = (2x - 1)(2x+1) б) (у+1)^3 - y(y^2 + 3y) = 7

didar6 didar6    3   07.10.2019 08:41    6

Ответы
sargsyana524 sargsyana524  10.10.2020 01:14

Надеюсь, что тебе будет все понятно.


1. выражение: а) (х-3)(х+3) + (х+3)^2 б) (у-4)^2 - (4-у)(4+у) 2. решите уравнение: а) (2х + 3)^2 - 7
ПОКАЗАТЬ ОТВЕТЫ
elenafedorova elenafedorova  10.10.2020 01:14
A)(x-3)(x+3)+(x+3)²=(x-3)²+(x+3)²

б)(y-4)²-(4-y)(4+y)=(y-4)²-(4-y)²

№2

РЕШЕНИЕ:

a)(2x+3)²-7x=(2x-1)(2x+1)

4x²+12x+9-7x=4x²+2x-2x-1

4x²+5x -4x²=-1-9

5x=-10

x=-10/5

x=-2

ОТВЕТ:-2

РЕШЕНИЕ:

б) (y+1)³-y(y²+3y)=7

y³+3y²+3y+1-y³-3y²=7

3y+1=7

3y=7-1

3y=6

y=6/3

y=2

ОТВЕТ: 2
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра